2010
DOI: 10.1007/s10792-010-9353-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined phacoemulsification and viscogoniosynechialysis in the management of patients with chronic angle closure glaucoma

Abstract: The purpose of this study was to evaluate the effectiveness of phacoemulsification and viscogoniosynechialysis in the management of patients with chronic angle-closure glaucoma (CACG). Fifty-six eyes of 45 recruited patients were classified into two groups: group 1 had medically controlled CACG (IOP 21 mmHg with maximum tolerated medications) including 21 eyes. All of the patients had at least one quadrant without peripheral anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…To open the PAS after cataract surgery, a viscoelastic agent is injected into 360° of the anterior chamber angle. Previous studies have shown that combined phacoemulsification and viscogoniosynechialysis are effective in lowering IOP [17,18,24]. These findings were comparable to our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To open the PAS after cataract surgery, a viscoelastic agent is injected into 360° of the anterior chamber angle. Previous studies have shown that combined phacoemulsification and viscogoniosynechialysis are effective in lowering IOP [17,18,24]. These findings were comparable to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Third, in those eyes that undergo combined phacoemulsification and viscogoniosynechialysis, if the IOP is not sufficiently controlled, it is more convenient to perform trabeculectomy at a later stage. As the corneal incision used in combined phacoemulsification and viscogoniosynechialysis is transparent, there is no need to consider conjunctival scarring [24]. …”
Section: Discussionmentioning
confidence: 99%
“…12 Microcoaxial phacoemulsification has advantages over standard coaxial phacoemulsification, and the learning curve is less steep when converting from a standard coaxial technique. 13,15 The microincision technique protects the Data were represented as median (range, minimum to maximum), and compared using the Wilcoxon signed-rank test.…”
Section: Discussionmentioning
confidence: 99%
“…ACD indicates anterior chamber depth; BCVA, best corrected visual acuity; CECC, corneal endothelial cell count; IOP, intraocular pressure; SIA, surgically induced astigmatism. biomechanics and prolate shape of the cornea 17 and results in less SIA and improved visual quality, 15,18 along with rapid wound healing 16,17 and visual rehabilitation, 18 less inflammation, and lower risk of endophthalmitis. 22 It also induces less astigmatism and reduces all intraoperative phaco parameters except total surgical time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation